2015
DOI: 10.1007/s00221-015-4201-4
|View full text |Cite
|
Sign up to set email alerts
|

Activation patterns of different brain areas during incremental exercise measured by near-infrared spectroscopy

Abstract: Recent studies postulated that increased oxygenation of the prefrontal cortex (PFC) during elevating exercise intensities reflects a specific activation of this region. Furthermore, the drop in PFC oxygenation often measured shortly before exhaustion is interpreted as a main factor limiting exercise. Nevertheless, a limitation of these studies is that they often measured NIRS only in the PFC. Within this study, we hypothesized that these findings are not region specific but rather result from systemic blood re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 31 publications
3
46
0
Order By: Relevance
“…In the present study, no decline in cerebral oxygenation was observed at a similar intensity; instead, cerebral oxygenation increased in the high-tolerance and remained stable in the low-tolerance group. The lack of a drop in PFC oxygenation near exhaustion has recently been observed by others (Jung et al, 2015). A potential explanation of this discrepancy is that it may be due to differences in the placement of the optodes over the PFC (Jung et al, 2015), since prior work has shown region-specific changes in PFC hemodynamics (Tempest, Eston, & Parfitt, 2014).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In the present study, no decline in cerebral oxygenation was observed at a similar intensity; instead, cerebral oxygenation increased in the high-tolerance and remained stable in the low-tolerance group. The lack of a drop in PFC oxygenation near exhaustion has recently been observed by others (Jung et al, 2015). A potential explanation of this discrepancy is that it may be due to differences in the placement of the optodes over the PFC (Jung et al, 2015), since prior work has shown region-specific changes in PFC hemodynamics (Tempest, Eston, & Parfitt, 2014).…”
Section: Discussionmentioning
confidence: 89%
“…The lack of a drop in PFC oxygenation near exhaustion has recently been observed by others (Jung et al, 2015). A potential explanation of this discrepancy is that it may be due to differences in the placement of the optodes over the PFC (Jung et al, 2015), since prior work has shown region-specific changes in PFC hemodynamics (Tempest, Eston, & Parfitt, 2014). Finally, both males and females took part in this study, and no gender effects were observed (other than those likely explained by fitness).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, considering that NIRS measurements reflect but region-specific oxygenation changes, we cannot exclude that other brain areas, critically involved in strenuous exercise (cf. Jung et al 2015), were affected by SUSOPS.…”
Section: Discussionmentioning
confidence: 99%
“…Near infrared spectroscopy (NIRS) is commonly used to examine the cerebral haemodynamic response (oxygenation [O 2 Hb; oxygen delivery], deoxygenation [HHb; oxygen extraction] and total blood volume [tHb = O 2 Hb + HHb]) during exercise (Ferrari & Quaresima, ). Many studies focus largely upon prefrontal areas of the brain during exercise in healthy (Shibuya et al ., ; Bhambhani et al ., ; Hiura et al ., ; Rupp et al ., ; Tempest et al ., ; Jung et al ., ) and clinical populations (Neary et al ., ; Fu et al ., ; Lin et al ., ; Vogiatzis et al ., ). The predominant modes of exercise used in such studies are upright and recumbent cycle ergometers.…”
Section: Introductionmentioning
confidence: 99%